2010
DOI: 10.1080/19440049.2010.517568
|View full text |Cite
|
Sign up to set email alerts
|

Saturated and aromatic mineral oil hydrocarbons from paperboard food packaging: estimation of long-term migration from contents in the paperboard and data on boxes from the market

Abstract: In the absence of a functional barrier, mineral oil hydrocarbons from printing inks and recycled fibres tend to migrate from paper-based food-packaging materials through the gas phase into dry food. Concentrations easily far exceed the limit derived from the acceptable daily intake (ADI) of the Joint FAO/WHO Expert Committee on Food Additives (JECFA). Since the estimation of long-term migration into the food by testing at 40°C for 10 days is difficult, it seems preferable (and easier) to use the mineral oil co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…Since recycled board is not used for liquid food contact, migration is limited to the components of sufficient volatility enabling transfer through the gas phase, which is up to about C 24 (Lorenzini et al, 2010). This means that the offset printing inks are of primary concern particularly those used for newspaper .…”
Section: Recycled Boardmentioning
confidence: 99%
See 1 more Smart Citation
“…Since recycled board is not used for liquid food contact, migration is limited to the components of sufficient volatility enabling transfer through the gas phase, which is up to about C 24 (Lorenzini et al, 2010). This means that the offset printing inks are of primary concern particularly those used for newspaper .…”
Section: Recycled Boardmentioning
confidence: 99%
“…Extraction needs to be complete for the relevant MOSH and MOAH, be in a solvent adequate for the pre-separation and -in the case of certain packaging materials -discriminate from the high molecular mass hydrocarbons, such as hot melts and polyethylene oligomers which disturb GC analysis (Lorenzini et al, 2010).…”
Section: Extractionmentioning
confidence: 99%
“…In the foods, MOSH and MOAH from sources other than migration from the paperboard were subtracted as far as possible (Biedermann, Ingenhoff, Zurfluh, et al Forthcoming 2013). For the analysis of paperboard, another cut was introduced at the end of the peak of n-C 24 , beyond which migration at ambient temperature into dry food becomes negligible (Lorenzini et al 2010). Measurement uncertainty was primarily determined by the interpretation of the chromatograms.…”
Section: Methodsmentioning
confidence: 99%
“…In the range between n-C 18 and n-C 24 , for which a substantial migration is still observed for long-term storage at ambient temperature, temperature increase accelerates significantly. Beyond n-C 24 , there is little migration at ambient temperature (Lorenzini et al 2010; many chromatograms in The cut between the migration observed at room temperature and that added by temperature increase is slanted because the distinction between migrating and non-migrating substances is not sharp. In the chromatograms of Figure 2, it is simplified by a straight line and the effect of warming shown by arrows.…”
Section: Effect Of Temperature Increase On Mass Rangementioning
confidence: 95%
“…They do not deal with the migration of compounds of a volatility below this cut-off into dry foods (the subject of the present paper). Lorenzini et al (2010) determined that during extended storage at ambient temperature mineral oil hydrocarbons migrated substantially up to those eluted from GC on a non-polar stationary phase at n-C 24 (boiling point of n-C 24 , 391°C), without this cut being sharp (there may also be some migration up to about n-C 28 ). Again the question was not addressed whether there could also be migration of higher boiling (essentially involatile) substances by a mechanism other than gas phase transfer.…”
Section: Introductionmentioning
confidence: 99%